Seismic Performance Assessment of Existing RC Frames with Different Ultimate Concrete Strains - Rishath Sabrin; Mohammad Al Amin Siddique; Md. K. Sohel (Civil Engineering Journal, 2018)
In recent years, because of the older version code, inadequate design, lacks of construction supervision, change in loading pattern, damages and casualties of earthquakes or environmental degradation, buildings at risk need to be investigated frequently for safety purpose. To increase the strength and ductility capacities of deficient reinforced concrete (RC) beams, columns and beam-column joints, retrofitting may require. In this paper, a numerical investigation using nonlinear static pushover analysis is conducted to assess the seismic behavior of existing moment resisting RC frames. In numerical modeling, different plastic hinge lengths as well as different concrete ultimate strain conditions of RC members are considered. Pushover analysis has been carried out with the commercial software ETABS v.9.6.0 to evaluate structural behavior of RC frames located in a seismic region. Hinge properties simulating moment-rotation behavior of frame members considering different plastic hinge lengths as well as concrete ultimate strains are evaluated. Pushover curves are compared with each other to determine the plastic hinge length and strain values which provide better agreement with that of the default properties. Seismic performance criteria in terms of ductility, overstrength as well as response modification factor for frames are determined from pushover curves. From the analyses in general, the load carrying capacity as well as displacement at maximum lateral load and interstory drift index at any floor level of RC frames is assessed.